No easy way : the story of Ted Williams and the last .400 season - Bowen, Fred (Dutton Children's Books, 2010)
Ted Williams hit .406 for the season in 1941--a feat not matched since. In this inspirational picture book, authentic sports writing and rich, classic illustrations bring to life the truly spectacular story of the Red Sox legend, whose hard work and perseverance make him the perfect role model for baseball enthusiasts of all ages.